2018
DOI: 10.1111/jch.13299
|View full text |Cite
|
Sign up to set email alerts
|

Fixed‐dose combinations: A valuable tool to improve adherence to antihypertensive treatment

Abstract: Hypertension is a major modifiable cardiovascular risk factor. [1][2][3] Several studies have shown that management of hypertension with all five main classes of blood pressure (BP)-lowering drugs (diuretics, β-blockers, calcium channel blockers, angiotensin-converting enzyme inhibitors, and angiotensin receptor blockers) substantially reduces cardiovascular morbidity and mortality. 4 However, only a minority of patients with hypertension achieve BP targets. 5-7 An important contributor to these low rates of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…A significant advantage of using FDCs is to reduce therapeutic inertia to manage hypertension allowing for simultaneous uptitration of dose as applicable [51]. Other benefits include improved medication compliance and adherence, decreased pill burden, increased efficacy, and fewer AEs owing to the complementary effect of the combinations used versus single doses [52,53]. The safety findings in our study are complementary to and aligned with the known safety profile of FDCs studied previously.…”
Section: Table 2 Continuedsupporting
confidence: 79%
“…A significant advantage of using FDCs is to reduce therapeutic inertia to manage hypertension allowing for simultaneous uptitration of dose as applicable [51]. Other benefits include improved medication compliance and adherence, decreased pill burden, increased efficacy, and fewer AEs owing to the complementary effect of the combinations used versus single doses [52,53]. The safety findings in our study are complementary to and aligned with the known safety profile of FDCs studied previously.…”
Section: Table 2 Continuedsupporting
confidence: 79%
“…One significant advantage is the potential for FDCs to reduce clinical or therapeutic inertia in the control of hypertension, since two drugs would be introduced or up‐titrated simultaneously . Additional key advantages and benefits include increased efficacy, decreased pill burden, improved medication adherence, and reduction (mitigation) in side effects and adverse events of a given single agent when it is used as monotherapy . In practical terms, clinical data have shown that the use of FDCs in the form of a single pill or capsule, when compared to combination therapy involving separate single agents, in the long term can be cost‐effective .…”
Section: Fixed‐dose Single‐pill Combination Therapy In Hypertensionmentioning
confidence: 99%
“…16 The suboptimal control of these risk factors is due to many causes, including physician inertia, side effects, and cost of treatment. 17 However, a major contributor to the low rates of achievement of BP and LDL-C targets appears to be suboptimal adherence to antihypertensive and lipid-lowering treatment. 18,19 On the other hand, previous studies suggested that fixed-dose combination of statins and antihypertensive agents results in better adherence to treatment than separate pill combination.…”
Section: Hypertension and Elevated Low-density Lipoprotein Cholesterolmentioning
confidence: 99%
“…Accordingly, among patients with hypercholesterolemia who are receiving lipid‐lowering treatment, LDL‐C targets are achieved in approximately two thirds of patients . The suboptimal control of these risk factors is due to many causes, including physician inertia, side effects, and cost of treatment . However, a major contributor to the low rates of achievement of BP and LDL‐C targets appears to be suboptimal adherence to antihypertensive and lipid‐lowering treatment .…”
mentioning
confidence: 99%